The Influence of Perceived Maternal Warmth toward Empathy among Urban Adolescents from Low Socio-Economic Status Family - Amanda Rachmawati; Ratih Arruum Listiyandini (PSIKODIMENSIA, 2020)
This study aims to investigate how far maternal warmth can prredict empathy among urban adolescents who are living in the poverty condition. Sample in this study were 202 adolescents coming from low socio-economic status family in Jakarta, chosen with purposive sampling technique. The instruments that were used are Basic Empathy Scale and subscale of warmth/affection from Parental Acceptance-Rejection Questionnaire. Regression analysis indicate that maternal warmth has signitificant and positive role towards empathy among adolescents living in poverty condition by 7 %. Maternal warmth is also known to contribute on the affective empathy by 2,9 % and on the cognitive empathy by 8,7 %. The results of this study are expected to be a reference to develop educational programs for adolescents and mothers who live in poverty for preventing moral transgression among this population. Keywords: adolescent; empathy; maternal warmth; poverty.